Wearable Embedded System Design and Development for Hydration Monitoring via Bio impedance Analysis - Chauhan, Rahul (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
In terms of human physiology, water is the single most important factor in ensuring optimal health. As a universal medium, it is essential to every function in the body. Dehydration is a common ailment that may occur when there is an abnormal loss of bodily fluids. Physical and cognitive abilities are both hampered by dehydration. In this study, we discuss the ideation, design, and implementation of a wearable embedded device that can detect a person's fluid status. Wearable medical devices (WMDs) are on the rise in the biomedical industry because they provide a patient management system, guarantee patients' physical and mental health via constant monitoring, and lower the financial and logistical barriers to providing medical care anywhere. This work use bioelectrical impedance analysis (BIA), one of various methods for tracking fluid intake.